(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Wood-plastic composites (WPCs) have excessively taken place in the construction industry in recent years. The high technological properties are crucial for WPCs when utilized as structural members. In this study, flat-pressed WPCs produced with polypropylene (PP) were reinforced with woven glass fiber fabric to enhance their properties. The effect of intensity of woven fabric (195 gr/m2 and 390 gr/m2) and wood flour content (40, 50, 60%) on WPCs’ physical and mechanical properties were investigated. The addition of a coupling agent (CA) positively influenced WPCs’ mechanical properties and restricted water absorption. However, water absorption increased with an increase in wood flour content. The increase in water exposure time from 1 day to 30 days increased water absorption up to 37%. In terms of water absorption, there was no significant difference between reinforced WPCs and controls. The reinforcement of WPCs improved mechanical properties significantly; i.e., flexural strength was increased up to 252%, while tensile strength reached up to 667%. As expected, the increase in wood flour content decreased mechanical properties. The incompatibility between wood flour and PP negatively influenced WPCs properties. It could be concluded that, if configured appropriately to the usage conditions, flat-pressed WPCs reinforced with woven glass fiber fabric have a potential for areas where high strength is required.